2000
DOI: 10.2460/ajvr.2000.61.1566
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance energy requirements and the effect of diet on performance of racing Greyhounds

Abstract: Racing Greyhounds ran faster when fed a diet containing higher fat and protein and lower carbohydrate contents. Their maintenance metabolizable energy requirement was slightly higher than that of moderately active dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Many of the serum biochemical alteration due to exercise were similar to those observed in other Greyhound studies [3] [5] [17] [19], showing rises in sodium and decreases in bicarbonate and chloride in the initial 10 minutes after exercise; while some studies found no alterations in chloride or potassium [4] [5]. The change in sodium is likely related to the increased osmolality post-exercise, while bicarbonate would be expected to fall as a compensatory mechanism for expected post-exercise lactic acidosis and rapid exchange of carbon dioxide due Table 2.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Many of the serum biochemical alteration due to exercise were similar to those observed in other Greyhound studies [3] [5] [17] [19], showing rises in sodium and decreases in bicarbonate and chloride in the initial 10 minutes after exercise; while some studies found no alterations in chloride or potassium [4] [5]. The change in sodium is likely related to the increased osmolality post-exercise, while bicarbonate would be expected to fall as a compensatory mechanism for expected post-exercise lactic acidosis and rapid exchange of carbon dioxide due Table 2.…”
Section: Discussionsupporting
confidence: 67%
“…These dogs were consuming about twice that amount [25]. In addition, the higher kilocalorie consumption for daily energy requirements in Greyhounds leads to a 20% increase in consumption of all the mineral and vitamins intakes recommended [4], therefore many of the vitamin and mineral intakes might have been adequate due to the slightly higher energy intake of these dogs when compared with normal house dwelling domestic pet dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative samples of food and all feces produced by the dogs over 4 days during weeks 8 and 17 were collected and stored at -20 o C. Nutrient composition, apparent digestibility, and ME of the food samples were measured as previously described. 1 The masses of crude protein, fat, ash, insoluble fiber, and moisture were subtracted from total mass of food to obtain the mass of nitrogen-free extract (NFE) in the food. This NFE provided a measure of the carbohydrate content of the diet.…”
Section: Methodsmentioning
confidence: 99%
“…For competitive sprint and endurance canine athletes, optimal nutrition is required for dogs to perform at their peak. Dietary recommendations are specific for sprint (Hill et al 2000) and endurance athletes (Reynolds et al 1999;Toll & Reynolds 2000), although general recommendations for both activities include high digestibility, low bulk, higher fat and protein, and lower carbohydrate dietary content, compared with an adult maintenance diet.…”
Section: Comparison With Wild Speciesmentioning
confidence: 99%